Barsel i berget - Weisser, Hanne (Tidsskrift for kulturforskning, 2016)
The Scandinavian medieval ballad "Liti Kjersti og bergekongen" (TSB A 54) is in this essay being read in a social historical context: The history of hidden pregnancy, childbirth and infanticide. It is argued that infanticide, being a social problem in Scandinavian soci-eties in the 17th, 18th and 19th century, is the underlying theme in this ballad. A question raised is whether the ballad reflects a will to understand the situation of the women who had committed infanticide, in contrast to the attitude reflected in the law in these centuries, sentencing to death those who were found guilty in this crime. The variant written down in Telemark in 1857 after Bendik Aanundson, is here being read parallel to the court material from a criminal case which took place in 1818 in Fyresdal in Telemark, where a young, unmarried maid was found guilty in committing infanticide. The storyline in the ballad is being discussed in relation to the social condi-tions, moral laws and women’s legal position in premodern Norway. Also verses and stan-zas from other variants of "Liti Kjersti og bergekongen" are drawn upon for the purpose of supplementing the variant after Bendik Aanundson, as they exemplify the rich, varied and broad tradition of this ballad.